Is Szabolcsi’s logic a fuzzy logic? - Castro-Manzano, J.-Martín (Universidad Panamericana, 2024)
In this paper we ask ourselves whether Szabolcsi’s numerical term logic is a fuzzy logic. Our answer is in the affirmative. In order to justify such a claim, we first expound some preliminaries that help us understand why the inclusion of fuzzy quantifiers is a sufficient condition for fuzziness. Then we present Szabolcsi’s logic, which includes said quantifiers.
¿Es la lógica de Szabolcsi una lógica difusa?
1. Introduction -- 2. Preliminaries -- 3. Szabolcsi’s logic -- 4. Final remarks
Keywords: Lógica de términos; Lógica numérica; Lógica difusa; Term logic; Numerical logic; Fuzzy logic